Carbon nanotube ecotoxicity in amphibians: assessment of multiwalled carbon nanotubes and comparison with double-walled carbon nanotubes. (August 2010) - Mouchet, Florence; Landois, Perine; Puech, Pascal; Pinelli, Eric; Flahaut, Emmanuel; Gauthier, Laury
The potential impact of industrial multiwalled carbon nanotubes (MWNTs) was investigated under normalized laboratory conditions according to the International Standard micronucleus assay ISO 21427–1 for 12 days of half-static exposure to 0.1, 1, 10 and 50 mg/l of MWNTs in water. Three different end points were carried out for 12 days of exposure: mortality, growth inhibition and micronuclei induction in erythrocytes of the circulating blood of larvae. Raman spectroscopy analysis was used to study the presence of carbon nanotubes in the biological samples. Considering the high diversity of carbon nanotubes according to their different characteristics, MWNTs were analyzed in Xenopus larvae, comparatively to double-walled carbon nanotubes used in a previous study in similar conditions. Growth inhibition in larvae exposed to 50 mg/l of MWNTs was evidenced; however, no genetoxicity (micronucleus assay) was noticed, at any concentration. Carbon nanotube localization in the larvae leads to different possible hypothesis of mechanisms explaining toxicity in Xenopus .